(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
A punctual analysis on the former, strict ban on assisted reproduction with gamete donation in Italy – established by law no. 40/2004 – and its following, progressive “demolition” by the Italian Constitutional Court (especially by the recent judgement no. 162/2014). A reflection about the criteria applied by the Court, the role of the European Court of Human Rights and the future, desirable legislation on ethically sensitive subjects.